Pancolitis with Ischemic Injury as a Complication of Immunosuppressive Treatment in a Patient with Autoimmune Hepatitis: A Case Report. (31st December 2012) - Dalbeni, A.; Capoferro, E.; Bernardoni, L.; Capelli, P.; Caliò, A.; Gabbrielli, A.; Capra, F.
Abstract : Ischemic colitis is a serious drug-induced adverse event. There are only few cases of immunosuppression-associated ischemic colitis described in the literature, but none with a pancolitis-like manifestation. We report the case of a 72-year-old female patient who developed a pancolitis with ischemic injury on immunosuppressive treatment with steroids and azathioprine for autoimmune hepatitis. The patient presented with massive rectal bleeding. Colonoscopy confirmed the diagnosis of pancolitis. The results of histological examination indicated drug-induced ischemic colitis involving the entire colon. This is the first case of ischemic pancolitis mimicking an inflammatory bowel disease (IBD) in a patient with immunosuppressive therapy.